Recent developments in selective therapeutic targeting of functionalized nanomaterials to neurovascular units in overcoming the gaps in neurovascular therapy - Sakshi Goswami; Nickolay K. Isaev; Alla B. Salmina; Suresh Vir Singh Rana; Sergey N. Illarioshkin; Yeshvandra Verma (Brain Disorders)
Neurodegenerative disorders are difficult to treat because of natural barrier in the brain. Moreover, neurovascular units seem to be essential targets/mediators of the nervous system cytoprotective effects. Functionalized nanomaterials have gained significant prominence in the medical domain due to their extensive utilization in targeted drug delivery and therapeutics within the neurovascular system. Their remarkable potential in neurovascular therapy has been demonstrated, highlighting their effectiveness in this field. A systematic summary of the specific applications and limitations of functionalized nanomaterials in the targeted delivery system is essential for developing smart therapies to overcome the gaps in neurovascular therapy for the treatment of neurological disorders. The objective of present article was to highlight the advancements in recent therapies support the potential role of functionalized nanomaterials to tackle the difficulties in targeted delivery systems for neurodegenerative disorders. We review the role of functionalized nanomaterials as therapeutics within the neurovascular units and their potential to lead to more sophisticated and smart treatment techniques despite some obstacles, given to the patients of neurological disorders, particularly when paired with multimodal drugs who are likely to benefit from cytoprotection. This review also addresses the current understanding, gaps, and issues to be resolved.